Racism and Labor in Brazil: From Colonial Roots to Neoliberal Capitalism - Madeira, Maria Zelma de Araújo; Gomes, Daiane Daine de Oliveira (Argumentum, 2024)
The labor market is one of the spheres that unequivocally expresses the persistent structure of racial inequality in Brazilian social dynamics. Thus, this study aims to briefly analyze aspects that contribute to understanding the complexity of racism in social relations under Brazilian dependent capitalism. To this end, a bibliographic research was conducted grounded in the principles of historical materialism, highlighting how colonialism, slavery, and abolitionism without rights guarantee are fundamental elements for understanding the configurations of current labor relations. It is concluded that racism remains one of the main mechanisms responsible for the precarious inclusion or exclusion of Black individuals from the labor market, and that the advancement of neoliberalism has maximized the processes of racial domination and the racialization of poverty.